Management of primary ciliary dyskinesia/Kartagener's syndrome in infertile male patients and current progress in defining the underlying genetic mechanism - Yan-Wei Sha; Lu Ding; Ping Li (Asian Journal of Andrology, 2014)
Kartagener's syndrome (KS) is an autosomal recessive genetic disease accounting for approximately 50% of the cases of primary ciliary dyskinesia (PCD). As it is accompanied by many complications, PCD/KS severely affects the patient's quality of life. Therapeutic approaches for PCD/KS aim to enhance prevention, facilitate rapid definitive diagnosis, avoid misdiagnosis, maintain active treatment, control infection and postpone the development of lesions. In male patients, sperm flagella may show impairment in or complete absence of the ability to swing, which ultimately results in male infertility. Assisted reproductive technology will certainly benefit such patients. For PCD/KS patients with completely immotile sperm, intracytoplasmic sperm injection may be very important and even indispensable. Considering the number of PCD/KS susceptibility genes and mutations that are being identified, more extensive genetic screening is indispensable in patients with these diseases. Moreover, further studies into the potential molecular mechanisms of these diseases are required. In this review, we summarize the available information on various aspects of this disease in order to delineate the therapeutic objectives more clearly, and clarify the efficacy of assisted reproductive technology as a means of treatment for patients with PCD/KS-associated infertility.